El Excentrico, 1966-07-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 20, 1966 [20 de Julio de 1966]. No volume or issue number. Cover has a picture of two women showing an adtertisement for the Club San Felipe 7th Anniversary Dance, which took place at the Little New Yorker on July 30.